Combining the zebrafish embryo developmental toxicity assay (ZEDTA) with hemoglobin staining to accelerate the research of novel antimalarial drugs for pregnant women - Lucia Borrallo-Lopez; Laura Guzman; Noelia G. Romero; Anna Sampietro; Ana Mallo-Abreu; Laia Guardia-Escote; Elisabet Teixidó; Burkhard Flick; Xavier Fernàndez-Busquets; Diego Muñoz-Torrero; Marta Barenys (International Journal for Parasitology: Drugs and Drug Resistance)
Background: Malaria during pregnancy implies a high risk for the mother and the developing child. However, the therapeutic options for pregnant women have historically been very limited, especially during the first trimester of pregnancy due to potential adverse effects on embryo-fetal development. Recently, there has been great controversy regarding these potential embryo-fetal adverse effects because the results of rodent studies were not in accordance with the clinical data available, and finally the WHO has changed the recommendations for pregnant women with uncomplicated P. falciparum malaria to treatment with artemether-lumefantrine during the first trimester. The discrepancy between pre-clinical and clinical studies has been attributed to species-differences in the duration of the window of susceptibility of circulating primitive erythroblasts. Methods: Here we provide a tool based on an alternative method to animal experimentation that accelerates the research of novel drugs for pregnant women. We have adapted the zebrafish embryo developmental toxicity assay to include hemoglobin staining in the embryos and two time-points of lethality and dysmorphogenesis evaluation. These two time-points were selected to include one when the development is independent of and one when the development is dependent of erythrocytes function. The method was used to test four marketed antimalarial drugs and three new antimalarial drug candidates. Results: Our combination of tests can correctly predict the teratogenic and non-teratogenic effects of several antimalarial marketed drugs (artemisinin, quinine, chloroquine, and dihydroartemisinin + desbutyl-lumefantrine). Furthermore, we have tested three new drug candidates (GS-GUAN, DONE3TCl, and YAT2150) with novel mechanisms of action, and different from those of the marketed antimalarial drugs. Conclusions: We propose a decision tree combining the results of the two time-points of evaluation together with the information on significant erythrocyte depletion. The aim of this decision tree is to identify compounds with no or lower hazard on teratogenicity or erythrocyte depletion at an early phase of the drug development process.